SERANGAN HAMA PADA TANAMAN KAYUBAWANG (Dysoxylum mollissimum Blume.) DI PROPINSI BENGKULU DAN SUMATERA SELATAN - KURNIAWAN, AGUS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Dysoxylum mollissimum Blume. is one of the most important tree species and widely planted in Bengkulu. The plant has also been planted in Kemampo Forest Research Station in South Sumatera. The research was done to know the species of pest attacking D. mollissimum, the distribution, attack intensity and severity, and the relationship between the tannin content of the plant and the pest attack. Observation on the pest attacking the plant was done in one year old stand in South Sumatera and 6-9 years old stand in Bengkulu. Tannin content was determined in healthy and attacked individual of the plant. The results showed that stem borer Xystrocera globosa attacked the plant in South Sumatera, while two species of bagworm Pteronema plagiopheps (Hamson.) and Pagodiella sp. were found in Bengkulu. The bagworms were not destructive to the plant. Stem borer X. Globosa was very destructive, made hole in the stem and killed some individual of the trees. The attack intensity and severity were low (5.93 % and 3.52%) The attack was decreasing tall and diameters plant growth (6,77%